THE EFFECTS OF FIRM INNOVATION ON FIRM DIVERSIFICATION AND PROFITABILITY: MEDIATING EFFECT OF FINANCIAL RISK MANAGEMENT (Contemporary Journal of Social Science Review, 2025)
The firm-level innovations are rapidly changing the corporate landscape of developing economies, and while it’s the great potential of these innovations that deserves to be investigated, it is the great potential of how these innovations impact firm profitability and diversification and the role of financial risk management that are hugely underexplored. This research focuses on the impact of  firm innovations in diversification and profitability of selected non-financial companies in the Pakistan Stock Exchange (PSX) in the years of 2017 to 2024, to which 1,600 firm-year observations are collected.  The paper evaluates how firm innovation impacts firm diversification and profitability with the specific emphasis on the mediation of financial risk management. Innovation is regarded as a major strategic force that helps companies to venture into new markets, come up with diversified product lines and increase competitive edge. The study examines the impact of innovation activities on diversification strategies and financial performance using empirical data collected on firms in various industries. It shows that innovation by the firm has a positive and significant effect on diversification and profitability. Further, sound financial risk management is an important mediating factor in that it lessens uncertainty, stabilizes cash flow and facilitates sustainable growth that is based on innovation. Companies that have performed better in risk management are in a better position to transform innovation processes into profit-generating diversification processes. The study can fill the gap in the literature because it explains the significance of combining the approaches of innovation strategies and financial risk management to attain long-term profitability. The findings can provide useful information to managers and policymakers wishing to improve performance in firms by means of innovation and strategic risk management. We recommend withdrawal of 300 basis point effective interest rate to foster further diversification and job creation by means of regulatory sandboxes, equity-debt swaps, and R&D tax credits.